"Mtwara will be the New Dubai": dashed expectations, grievances, and civil unrest in Tanzania. Issue 3 (4th May 2019) - Must, Elise; Rustad, Siri Aas
ABSTRACT: When does inequality lead to conflict? Despite recent studies highlighting the effects of group exclusion, this question has not been fully answered. We argue that objective group inequality is not sufficient to fuel unrest. Structural inequalities need to be perceived as unfair, and become grievances, in order to spark mobilization. While most conflict scholars recognize this on a theoretical level, statistical tests of the effect of inequality on conflict almost exclusively rely on objective data. This limits their ability to distinguish when inequality is politically relevant and when it is not. Southern Tanzania is a case in point. Despite decades of marginalization, the population remained peaceful until natural gas was discovered, and the government was perceived to break their promises of local development. Demonstrating that objective regional inequalities have remained relatively constant, while group grievances seems to have increased, we argue that direct measures of grievances are needed to pinpoint when inequality becomes politically salient. Using novel survey data, we find that people who think that the region is treated unfairly have the highest likelihood of supporting and participating in civil unrest.